Financial Performance Analysis in Predicting Corporate Bankruptcy: Before and During the COVID-19 Pandemic - Purwaningsih, Sri; Pernamasari, Rieke (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study holds significant implications as it analyzes financial performance in predicting bankruptcy in retail sector companies before and during the COVID-19 pandemic. It is a part of the 3rd TKT measurement, providing a comprehensive analytical and experimental understanding. Financial performance is gauged through the Current Ratio (CR), debt-to-equity ratio (DER), and Return on Assets (ROA). The research method employed is a quantitative approach. By using the purposive sampling method, a sample of 22 companies was obtained, with 2 years of observation before the Covid-19 pandemic and 2 years during the Covid-19 pandemic. The research findings reveal that the CR and ROA variables had a positive effect on financial distress, while the DER variable did not affect financial distress. Furthermore, the study concludes that there was no difference in the potential for financial distress before and during the COVID-19 pandemic, providing a unique and intriguing perspective on the impact of the pandemic on the retail sector.